Analysis of the Role of the Capital Market in Indonesia's Economic Development: Challenges and Prospects in the Future - Daniel Parulian Lumbantoruan; Marthin Sun Friedriks Sitompul; Naek Gideon Simamora; Eko samuel Rivaldo Sinaga; M. Putera Wal-Asri; Feronica Simanjorang (LPPM Institut Studi Islam Sunan Doe, 2024)
This study aims to analyze the role of the capital market in economic development in Indonesia and the challenges and prospects for the future. The research method used is literature review with data sources from various book articles and related sources. The challenges and prospects for the capital market in the future show great potential for Indonesia's economic growth, but there are also a number of challenges that need to be overcome. These challenges include increasing knowledge and understanding of investment in the capital market for the public, reforming regulations and law enforcement in accordance with developments in the capital market, as well as increasing liquidity and developing market instruments. However, with the implementation of the right policies, empowering the middle class as potential investors, increasing capital market education, and incentives for companies that go public, the capital market has bright prospects as an attractive investment vehicle and encourages Indonesia's economic growth in the future.